The Inherent Logic and Developmental Tendency of the Practice of Building Socialism with Chinese Characteristics: A Structural Analytical Framework for the Questions of “Where Did China Come From?” and “Where Should China Go?”. - Qingxiang, Han; Jian, Zhang (Social Sciences in China, 2013)
30多年来的中国特色社会主义建设实践.内含“功能思维→政府主导→理论引领 →混合结构→人民主体”五个结构要素和相应的五个演进梯次;在中国特色社会主义 建设实践进一步发展的进程中,中国共产党人的重要责任和使命(执政为民)和人民 群众的新期待(实践创新),决定了其基本趋向应是在“深层结构→核心体制→运行 方式”三个层级上进行改革并力争实现重大突破,体现为“调整结构→改革体制→转 变方式→建构秩序”。 关键词: 中国特色社会主义建设实践 内在逻辑 结构分析 The practice of more than 30 years of building socialism with Chinese characteristics contains within it a five-step evolution: “functional thinking → government leadership → theoretical guidance → hybrid structure → the people in the principal position”; in the course of the further development of the practice of building socialism with Chinese characteristics, the important responsibility and mission of Chinese Communists (exercising governance for the people) and the new expectations of the people (innovative practice) determine that its basic tendency should be to carry out reform and breakthroughs at three levels: “deep structures → core institutions → operational means,” embodied in “structural adjustment → restructuring → change of methods → construction of order.”